Finite element study of effect of parameters on stress distribution of steel shim in elastomeric bearings. Issue 9 (July 2019) - Zhang, Rui-jun; Li, Ai-qun
Elastomeric bearings are widely used in various structures as a type of seismic isolation device, and accurately assessing the state of their stress is an essential step in the design of elastomeric bearings. This article aims to better understand the influencing factors of stress distribution on the steel shims and the effect of steel shim thickness on the critical behaviour of elastomeric bearings. First, theoretical analysis is conducted for investigating the influencing factors of the bearing's critical load capacity and stress distribution on the steel shim thickness. Then, a series of finite element models is employed to study the influence of steel shim thickness on the global performance of bearings, the stress distribution on steel shims at different locations and the effect of steel shim thickness on stress distribution. Combining the results of theoretical analysis and finite element analysis, we conclude that steel shim thickness has little obvious effect on the mechanical properties of the bearing under normal working conditions, but it has a significant influence on the distribution and change of the local stress. Especially, when the vertical load and the horizontal displacement of the bearing increases, the growth rate of stress on the upper steel shims is very fast and may enter the yield state first or even resulting in local damage.